THE RELATIONSHIP BETWEEN DRY EYE SYNDROME AND THE USE OF PERSONAL PROTECTIVE EQUIPMENT (PPE) IN HOSPITAL MEDICAL WORKERS): Poster Presentation - Observational Study - Ophthalmologist - NUR SHANI MEIDA; Prifina Windy Aulia; Yunani Setyandriana (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Background: The need to wear personal protective equipment (PPE) during a pandemic can cause dry eye syndrome. It will increase sweating so reduce tear production and the use of masks increase air flow to the eye area so that tear evaporation increases. Objective: To determine the relationship between the incidence of dry eye syndrome and the use of PPE in hospital medical personnel. Methods : Methods: This was an analytic observational study with a cross-sectional design using the OSDI (Ocular Surface Disease Index) questionnaire. The research was carried out at the Cilacap Hospital in 2021. There were 49 samples (51% male and 49% female), with an age range of 20-50 years. The data was analyzed by using the Spearmans test. Results : Results: The incidence of dry eye syndrome was 69.5% (mild 18.4%, moderate 18.4%, severe 32.7%). As many as 53.1% of the incidence of dry eye syndrome occurred in wearing PPE for more than 4 hours and was more common in the use of PPE level 1 (40.8%), followed by level 3 (36.7%) and level 2 (22.5%). In the Spearman's test, it was found that there was a significant association between the incidence of dry eyes syndrome and the use of PPE (duration and level of PPE) (p<0.05) but had a weak relationship strength (r=0.3). Conclusion : Conclusion: There is a significant relationship between the incidence of dry eyes syndrome and the use of PPE (duration and level of PPE use) but has a weak relationship strength.